Estimating the potential for solar energy utilization in Chile by satellite-derived data and ground station measurements. (November 2015) - Escobar, Rodrigo A.; Cortés, Cristián; Pino, Alan; Salgado, Marcelo; Pereira, Enio Bueno; Martins, Fernando Ramos; Boland, John; Cardemil, José Miguel
Highlights: Solar resource assessment for Chile is reported with measurements and satellite estimations. Effective cloud cover computations allow estimation of the global and diffuse irradiation. The model is validated by comparison with ground station data. Solar fraction of 80% is achievable for solar thermal systems; PV yield between 4.5 and 8 kW h/kWpv. CSP annual yields of up to 240 GW h/year for a 50 MW parabolic trough plant. Abstract: The progress in solar energy resource assessment for Chile is reported, including measurements from a ground station network spanning more than three years of data, satellite estimations from the recently developed Chile-SR model including three full years of data, and simulations that evaluate the potential for solar thermal, photovoltaics (PV) and concentrated solar power (CSP) utilization. The satellite estimation model adapts the Brasil-SR methodology with the combined use of visible and infrared (IR) satellite images, an enhanced treatment for altitude-corrected meteorological variables and an effective cloud cover computations that allows the estimation of the global horizontal and diffuse horizontal irradiation on an hourly basis. Direct normal irradiation (DNI) is computed from the direct horizontal irradiation by applying the Boland–Ridley–Laurent (BRL) model of diffuse fraction and proper solar geometry corrections. Comparison of the satellite-derived data with the ground station data shows good agreement and low error levels thus served for model validation. The results indicate that Chile is endowed with one of the highest levels of solar resource in the world in terms of annual irradiation for large portions of its territory. There is a small decrease in yearly levels of GHI and DNI with latitude that in practice indicate that most of the country shares exceptional conditions for solar energy. However, coastal regions have a large decrease in both GHI and DNI due to the persistence of seasonal cloud covers with daily cycles. The use of irradiation data from the Chile-SR model for system simulation indicates that solar fractions over 80% are achievable for residential-sized solar thermal systems in most of the country, with PV systems yielding between 4.5 and 8 kW h/kWpv, and CSP annual yields of up to 240 GW h/year for a 50 MW parabolic trough plant. These results indicate that the country has the potential for ample utilization of solar energy conversion technologies in most of its territory when considering annual GHI and DNI, suitable terrain availability and energy (electricity and heat) demand from industrial, commercial and residential activities.